Fabrication of thiophene decorated side chain entanglement free COFs for highly regenerable mercury extraction - Rajalakshmi, K.; Muthusamy, S.; Xie, M.; NAM, YUN SIK; Lee, Byeong hyeon; LEE, KANG BONG; Xu, Y.; Xie, J. (Elsevier BV, 2022)
The accumulation of mercury in the food chain and environment is harmful to living beings. This raises the need for high affinity, reusable cost-efficient adsorbents for mercury. Herein, we report a side chain entanglement free hetero atom effect bearing covalent organic framework MTF prepared by integrating melamine and thiophene linker. The AA stacked MTF-2 was prepared via transformation strategy from its AB stacked MTF-1 congener. The MTF-1 and MTF-2 were comprehensively analyzed through PXRD, SEM, TEM, 13C CP/MAS, N2 sorption and mercury removal efficiency. The adsorption capacity of MTF-2 revealed a value of 540 mg g？1, which is greater than that of MTF-1 (328 mg g？1). The adsorption mechanism was studied through XPS, 13C CP/MAS and XAFS indicating probable coordination of Hg2+ with both the triazine and sulfur moieties in a cooperative manner. To demonstrate the role of aromatic triazine ring, the analogous aliphatic triaminoguanidine was selected and the removal efficiencies between triaminoguanidine-thiophene COF (TAG-TF) and MTF-2 were compared. It revealed that the triazine unit containing MTF-2 showed 2.2 times greater removal efficiency than TAG-TF. The results reveal the structure-performance relationship, where the high surface area and relatively ordered functional moieties both paly a synergistic role in efficient mercury adsorption. ？ 2021 Elsevier B.V.